The role of public relations (PR) in the conduct of state language policy - Bigiri , Maryna (Theory and Practice of Public Administration, 2019)
The development of Ukrainian society in the direction of consolidation can not be imagined without a state language policy, the priority of which should be the development of the Ukrainian language as a unifying factor as the basis of our identity. Ukrainian language should provide all areas of life and public management relations, it must be used by the intellectual and political strata of Ukraine. The functional description of modern RR can be described by the following: - PR conducts regular, planned work, which is an integral part of management; - PR is monitoring mass consciousness, thoughts, relations and behavior of people; - PR analyzes the impact of the certain policy on the public; - PR modifies certain policy elements if they conflict with policy perspectives and public interest; - PR establishes and constantly supports the bilateral relations between the organization and the public; - PR deliberately carries out the necessary changes in thoughts, relations and behavior of people. A key element of working with PR is the impact on public opinion. Generality PR campaigns are conducted to: convince people to change their minds; to form a public opinion when it is not; strengthen the existing public opinion. For the public authorities, the most convenient and, according to the author opinion, the most effective way of public relations is to work with the media. In this context, not only the legislative regulation of linguistic relations, but also the promotion of the Ukrainian language, in particular, means of public relations, is of particular significance, which will enable them to capture them in the minds of people through repeatedly identifiable orientations and value systems.